MATH SOLVE

2 months ago

Q:
# How do u solve for b in the equation a square root + b square root =c square root

Accepted Solution

A:

Answer:Step-by-step explanation:you might be getting a bit confused here, that formula is the pyhthagorus theorem, which you use to solve the sides of a right angled triangle. if two of the sides of a right angled triangle are, lets say 3cm and 4cm, and you are trying to get the answer for the hypotenuse(the longest side, also the side opposite the right angle) then you do3²+4²=c²9+16=c²25=c²c=5(that was just an example btw)edit: im just going to keep that up there because it may be helpful, but i just realised you question.to find b in a²+b²=c²it would be easier if you knew the other two, like wayyyy easier.but what you would do is , lets say a was 3 and c was 5, then3²+b²=5² 9+b²=25b²=25-9b² =16b=√16b=4Hopefully this helps!!